Different Pulp Dressing Materials for the Pulpotomy of Primary Teeth: A Systematic Review of the Literature - Maurizio Bossù (Journal of Clinical Medicine, 2020)
Background: Pulpotomy of primary teeth provides favorable clinical results over time; however, to date, there is still not a consensus on an ideal pulp dressing material. Therefore, the aim of the present systematic review was to compare pulpotomy agents to establish a preferred material to use. Methods: After raising a PICO question, the PRISMA guideline was adopted to carry out an electronic search through the MEDLINE database to identify comparative studies on several pulp dressing agents, published up to October 2019. Results: The search resulted in 4274 records; after exclusion, a total of 41 papers were included in the present review. Mineral trioxide aggregate (MTA), Biodentine and ferric sulphate yielded good clinical results over time and might be safely used in the pulpotomies of primary molars. Among agents, MTA seemed to be the material of choice. On the contrary, calcium hydroxide showed the worst clinical performance. Although clinically successful, formocreosol should be replaced by other materials, due to its potential cytotoxicity and carcinogenicity. Conclusion: MTA seemed to be the gold standard material in the pulpotomy of primary teeth. Promising results were also provided by calcium silicate-based cements. Further randomized clinical trials (RCTs) with adequate sample sizes and long follow-ups are encouraged to support these outcomes.